Patron’s Day 2005 (Institutional Knowledge at Singapore Management University, 2005)
Recipients of Student Life Awards for outstanding achievements by students and co-curricular activity groups. The students are pictured with, from left to right, SMU President Howard Hunter, SMU Chancellor Lim Kim San, Singapore President and SMU Patron S R Nathan, SMU Chairman Ho Kwon Ping and SMU Provost Tan Chin Tiong. Photo from Patron’s Day 2005 held at Singapore Management University's Bukit Timah campus on 21 January 2005.